Helping Firms Realize the Benefits of (Partial) Formalization - Campos, Francisco; Goldstein, Markus; McKenzie, David (World Bank, Washington, DC, 2018)
Developing country governments seek to reduce pervasive informality of firms for multiple reasons: increasing the tax base, helping firms access formal markets and grow, increasing rule of law, and as a means of obtaining data that can be used for other government functions. The most common approach towards achieving these aims has been to make it easier for firms to formalize, most notably by setting up one-stop shops where firms can register as a legal entity and for tax purposes all at once. But past experiments have showed very few informal firms choose to formalize even after such reforms, and that many of those who do fail to see any benefits on financial access or firm growth. An alternative approach, used in much of Africa, is to separate the process of business registration from tax registration. Getting firms to register legally may help governments reduce informality and achieve some of the aims above, even if it does not raise more taxes. But the question is then whether firms are interested in even this more limited form of formalization, and whether they see any benefits from using it.